Risk Preferences in Participative Budgeting. - Kim, D.C. (The Accounting Review, 1992)
Examines participative budgeting in the context of the psychology of risk. Theoretical background on risk preferences; Empirical evidence of domain-specific risk preferences; Study design; Dispositional risk attitude measurement; Preference ratings of risk-averse versus risk-taking groups; Limitations of the study.